2020
DOI: 10.1080/10717544.2020.1818880
|View full text |Cite
|
Sign up to set email alerts
|

Type I collagen hydrogels as a delivery matrix for royal jelly derived extracellular vesicles

Abstract: Throughout the last decade, extracellular vesicles (EVs) have become increasingly popular in several areas of regenerative medicine. Recently, Apis mellifera royal jelly EVs (RJ EVs) were shown to display favorable wound healing properties such as stimulation of mesenchymal stem cell migration and inhibition of staphylococcal biofilms. However, the sustained and effective local delivery of EVs in nonsystemic approachessuch as patches for chronic cutaneous woundsremains an important challenge for the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…Recent reports from our group have demonstrated the presence of EVs in Apis mellifera bee-derived products such as royal jelly and honey. 8,12 In the present study, EVs from a monofloral source of honey such as Eucryphia cordifolia (Ec) were isolated employing a similar ultracentrifugation-based approach (HEc-EVs). These vesicles were found to be mostly in the size range of <150nm, with a mode of 138nm (Figure 1B), consistent with previous reports of exosome-like EVs derived from bee products.…”
Section: Honey-derived Extracellular Vesicles Contain Antibacterial Cargo and Specific Exosomal Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports from our group have demonstrated the presence of EVs in Apis mellifera bee-derived products such as royal jelly and honey. 8,12 In the present study, EVs from a monofloral source of honey such as Eucryphia cordifolia (Ec) were isolated employing a similar ultracentrifugation-based approach (HEc-EVs). These vesicles were found to be mostly in the size range of <150nm, with a mode of 138nm (Figure 1B), consistent with previous reports of exosome-like EVs derived from bee products.…”
Section: Honey-derived Extracellular Vesicles Contain Antibacterial Cargo and Specific Exosomal Markersmentioning
confidence: 99%
“…8 This promising antibacterial effect was also observed for bee-derived EVs released from type-I collagen matrixes, further displaying their potential as therapeutic agents for biofilm control. 12 Despite demonstrating the presence of EVs in bee-derived products, and their effect on human and bacterial cells, questions remain regarding their specific cargo as well as the mechanisms behind their observed antibacterial and antibiofilm effect. Furthermore, their potential effect on other Gram-positive biofilm-forming bacteria such as S. mutans and S. sanguinis has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The concurrent use of royal jelly with hydroxyapatite for bone healing has been reported; however, relevant literature is lacking in the combined use of royal jelly with biomaterials [ 76 ]. Very recently, extracellular vesicles of royal jelly were incorporated in a type I collagen matrix [ 72 ]. The released vesicles modulated the capacity of fibroblasts to migrate in vitro and were effective against S. aureus biofilm formation, thus demonstrating a potential delivery system for wound healing therapies.…”
Section: Scaffold Design and Experimental Studiesmentioning
confidence: 99%
“…Furthermore, the research group that first identified bee product-derived extracellular vesicles tried to develop novel type I collagen hydrogels as a continuous delivery matrix for royal jelly-derived extracellular vesicles [ 93 ]. Type I collagen hydrogels are well-established biomaterials for wound healing that can be also a local delivery system for EVs [ 107 , 108 ].…”
Section: Extracellular Vesicles As New Nutraceuticals From Bee Productsmentioning
confidence: 99%
“…Therefore, the combination of EVs and type I collagen may offer a number of benefits in wound healing therapies. Ramírez et al (2020) showed that the collagen concentration determines release patterns of royal jelly-derived extracellular vesicles and that gels containing 2 mg/mL collagen display the most stable release kinetics [ 93 ]. Released extracellular vesicles were biologically active as the integration into collagen did not alter their size or integrity.…”
Section: Extracellular Vesicles As New Nutraceuticals From Bee Productsmentioning
confidence: 99%